Oncological validation and discriminative ability of pentafecta criteria after open radical cystectomy. (28th September 2022) - von Deimling, Markus; Rink, Michael; Klemm, Jakob; Koelker, Mara; König, Frederik; Gild, Philipp; Khonsari, Maryam; Ludwig, Tim A.; Marks, Phillip; Dahlem, Roland; Fisch, Margit; Vetterlein, Malte W.
Abstract : Objectives: To validate the pentafecta criteria (PC) proposed by the PROMETRICS group for outcome reporting after radical cystectomy in an open radical cystectomy (ORC) cohort with long‐term follow‐up and to assess the discriminative ability of PC attainment for oncological endpoints. Patients and Methods: Between January 2009 and December 2017, 420 patients underwent ORC with pelvic lymph node dissection and urinary diversion for non‐metastatic bladder cancer. The PC were defined as reported by the PROMETRICS group. The primary endpoint was PC attainment, and oncological outcomes comprised further endpoints. We used uni‐ and multivariable logistic regression analysis to assess predictors of PC attainment. The discriminative ability of PC for overall mortality (OM), cancer‐specific mortality (CSM) and other‐cause mortality (OCM) was compared using Kaplan–Meier curves and cumulative incidence functions. After stratification by the number of PC attained, the association between PC attainment and the survival endpoints was tested on multivariable Cox regression and competing‐risks models. Results: A total of 108 patients (26%) fulfilled all PC, while 195 (46%), 77 (18%), 35 (8.3%) and five (1.2%) attained 4/5, 3/5, 2/5 and ≤1/5 PC, respectively. Increasing age‐adjusted Charlson comorbidity index (odds ratio [OR] 0.80, P = 0.015) and incontinent diversion (OR 0.38, P = 0.005) were independent predictors of PC non‐attainment. The median follow‐up was 73 months. PC attainment (≥4/5 vs 3/5 vs ≤2/5 PC attained) was used to stratify patients into groups at significantly different risk of death ( P < 0.001). A decreasing number of PC attained (<4/5) was associated with unfavourable survival estimates for both OM and CSM (all P ≤ 0.005) but not for OCM (all P ≥ 0.2). Conclusions: The PC proposed by the PROMETRICS group represent accurate quality indicators for oncological outcome reporting after ORC for non‐metastatic bladder cancer and have a distinct discriminative ability to predict long‐term OM and CSM.